Navidezna evidenca - resnična vizija - Puhar, Martin (Geodetski vestnik, 1997)
Virtual databases are the databases of the future. Virtual databases are based on Internet technology. Each user will have the potential to create their own databases. Particular data will be transfered to the user only when really needed. The data will be collected directly from original databases, therefore virtual databases will be as accurate as the original databases.
Keywords: evidence; geodezija; Internet; nepremičnine; podatkovne zbirke